Hongchoristites nomen novum: a replacement name for the Middle Triasic fossil Choristites Hong, 2005 (Insecta: Mecoptera: Permochoristidae) - Hernández, José Amet Rivaz (Zootaxa, 2018)
The fossil mecopteran genus Choristites was established by Hong in 2005, making Choristites martinsoni Hong, 2005 its type and only species. Hong placed this genus in family Permochoristidae Tillyard, 1917. The species was discovered from the Mid—Triassic Tongchuan Formation of Tongchuan region, Shaanxi Province and, until now, there have been no further records of Choristites martinsoni.